B2N2-Dibenzo[a,e]pentalenes: Effect of the BN Orientation Pattern on Antiaromaticity and Optoelectronic Properties - Wang, Xiao-Ye; Narita, Akimitsu; Feng, Xinliang; Muellen, Klaus (Journal of the American Chemical Society, 2015)
Two BN units were embedded in dibenzo[a,e]pentalene with different orientation patterns, which significantly modulated its antiaromaticity and optoelectronic properties. Importantly, the vital role of the BN orientation in conjugated molecules with more than one BN unit was demonstrated for the first time. This work indicates a large potential of the BN/CC isosterism for the development of new antiaromatic systems and highlights the importance of precise control of the BN substitution patterns in conjugated materials.
CRIS-Team Scopus Importer:2023-03-20